1999
DOI: 10.2307/2656618
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome numbers in Compositae. XVIII.

Abstract: Chromosome numbers and other cytogenetic data were determined from microsporocytes in 316 collections including 13 tribes of Compositae, mostly from Africa, Australia, Mexico, Central America, and South America. First reports are provided for 66 species and the genera Cassinia (2n ≈ 14(II)), Feldstonia (2n = 11(II)), Gochnatia (2n ≈ 23(II)), and Pseudoconyza (n = 10). In addition, new chromosome numbers are established at the generic level in Acourtia, Calea, Craspedia, Gnaphalium, Helipterum, Liabum, Leucheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
42
2
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 19 publications
9
42
2
3
Order By: Relevance
“…The present count of the 2n= 18 ( Fig. 1 and 2 D) is convenient with previously reported count of G. coronaria (Bhattacharyya 1977;Pavone et al 1981;Razaq et al 1988;Nirmala and Rao 1986;Vogt and Oberprieler 1993;Ruíz de Clavijo 1993;Oberprieler and Vogt 1993;Kaul and Kaur 1995;Strother and Watson 1997;Carr et al 1999;, and of G. coronaria var. discolor .…”
Section: Resultssupporting
confidence: 69%
“…The present count of the 2n= 18 ( Fig. 1 and 2 D) is convenient with previously reported count of G. coronaria (Bhattacharyya 1977;Pavone et al 1981;Razaq et al 1988;Nirmala and Rao 1986;Vogt and Oberprieler 1993;Ruíz de Clavijo 1993;Oberprieler and Vogt 1993;Kaul and Kaur 1995;Strother and Watson 1997;Carr et al 1999;, and of G. coronaria var. discolor .…”
Section: Resultssupporting
confidence: 69%
“…Philips (1982) recognized two sections for the N American species. In spite of the accumulating molecular data, chromosome information continues to be important in assessing phylogenetic relationships (Carr et al 1999). Although the cytological data on Parnassia is not complete, it was concluded that the basic chromosome numbers for the genus are x=7, 8 and 9.…”
Section: Discussionmentioning
confidence: 99%
“…16 '' and ''ca. 34'' (Robinson et al, 1981), and ''2n ϭ 32 II'' (Carr et al, 1999). Stenocarpha filiformis (Hemsl.)…”
Section: Methodsmentioning
confidence: 99%